2019
DOI: 10.1186/s12917-019-2160-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four commercially available ELISA kits for diagnosis of Fasciola hepatica in Irish cattle

Abstract: BackgroundFasciola hepatica is a liver parasite of mammals and it results in poor welfare outcomes and economic losses in ruminants. While faecal egg count is the test most commonly used for diagnosis, it does not indicate presence of migrating immature stages. Serological techniques increase sensitivity at all stages of the liver fluke infection. The aim of this study was to compare four commercially available ELISA tests for the diagnosis of F. hepatica. For this purpose, we tested three sample types; (i) kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 45 publications
0
13
1
Order By: Relevance
“…In the present study, breed of host showed insignificant association with fasciolosis; however, Anjum et al (2014) in Pakistan and Munita et al (2019) in Ireland found a significant association. Anjum et al (2014) documented a significantly higher frequency in Kajli (46.32%) breed followed in order by Lohi (37.43%), Cholistani (8.24%) and Thalli (7.90%).…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…In the present study, breed of host showed insignificant association with fasciolosis; however, Anjum et al (2014) in Pakistan and Munita et al (2019) in Ireland found a significant association. Anjum et al (2014) documented a significantly higher frequency in Kajli (46.32%) breed followed in order by Lohi (37.43%), Cholistani (8.24%) and Thalli (7.90%).…”
Section: Discussioncontrasting
confidence: 63%
“…Thus, most of the specialists are currently using enzyme-linked immunosorbent assay (ELISA) for the immuno-detection of Fasciola sp. (Rizwan et al, 2016;Acici et al, 2017;Munita et al, 2019).The excretory/secretory antigens (ES Ag)-based ELISA is explored which not only detects infection but also gives a better picture of the infection as compared to the conventional diagnostic techniques in the preventive management strategy of the Fasciola sp. in the livestock.…”
Section: Introductionmentioning
confidence: 99%
“…As herd size averages 40 animals, a total of four animals (~10% of herd size) aging 6 months and older, was randomly selected from 23 herds of Serra da Estrela sheep, located on 21 parishes of 4 municipalities of the region (Carregal do Sal, Celorico da Beira, Gouveia, and Seia). All 184 sera were screened for F. hepatica IgG antibodies, using a commercially available enzyme-linked immunosorbent assay (IDEXX Fasciola hepatica antibody test kit, Hoofddorp, the Netherlands), an assay based on the coating of microwells by f2 antigen of F. hepatica that has been shown to present 100% sensitivity and specificity [ 18 ]. Procedures were performed according to the manufacturer’s instructions, with samples being tested in duplicates.…”
Section: Methodsmentioning
confidence: 99%
“…The test is specific for detecting current infections, although challenging to use when the parasite burden is low. In addition, coproscopy does not detect non-reproducing immature stages and may also be unsuitable for large-scale and flock level testing [ 24 ].…”
Section: Diagnosismentioning
confidence: 99%